Cumulative live birth rates and birth outcomes after IVF/ICSI treatment cycles in young POSEIDON patients: A real-world study - Yan, Enqi; Li, Wenxuan; Jin, Huizi; Zhao, Mengya; Chen, Dan; Hu, Xinyao; Chu, Yifan; Guo, Yaxin; Jin, Lei (Frontiers in Endocrinology, 2023)
Objective The aim of this study was to describe the cumulative live birth rates (CLBRs) of young women with or without low prognosis according to the POSEIDON criteria after IVF/ICSI cycles and to investigate whether the diagnosis of low prognosis increases the risk of abnormal birth outcomes. Design Retrospective study. Setting A single reproductive medicine center. Population From January 2016 to October 2020, there were 17,893 patients (<35 years) involved. After screening, 4,105 women were included in POSEIDON group 1, 1,375 women were included in POSEIDON group 3, and 11,876 women were defined as non-POSEIDON. Intervention(s) Baseline serum AMH level was measured on the D2–D3 of menstrual cycle before IVF/ICSI treatment. Main outcome measure(s) Cumulative live birth rate (CLBR), birth outcomes. Result(s) After four stimulation cycles, the CLBRs in POSEIDON group 1, POSEIDON group 3, and non-POSEIDON group reached 67.9% (95% CI, 66.5%–69.3%), 51.9% (95% CI, 49.2%–54.5%), and 79.6% (95% CI, 78.9%–80.3%), respectively. There was no difference in gestational age, preterm delivery, cesarean delivery, and low birth weight infants between the three groups, but macrosomia was significantly higher in non-POSEIDON group, after adjusting for maternal age and BMI. Conclusion(s) The POSEIDON group shows lower CLBRs than the non-POSEIDON group in young women, while the risk of abnormal birth outcomes in the POSEIDON group will not increase.